Effect of 3D Printing Parameters on Dimensional Accuracy Using the Taguchi and Response Surface Methodology (RSM) - Ulhaq, Naswa Sabila; Islahudin, Nur (Tibuana, 2025)
Advances in technology in the manufacturing industry have driven the use of 3D printing as a fast and efficient prototyping solution. This study aims to optimize the process parameters of FDM 3D printing using PLA+ material with ASTM D-638-04 type specimens. The process parameters tested include printing speed, nozzle temperature, layer thickness, infill rate, and bed temperature, each at three levels. Optimization was performed using the Taguchi method and Response Surface Methodology (RSM), with a focus on dimensional accuracy (length, width, and thickness) as the primary response. The optimal parameters obtained from the Taguchi method are printing speed of 45 mm/s, nozzle temperature of 240°C, layer thickness of 0.30 mm, infill rate of 100%, and bed temperature of 55°C. Meanwhile, the RSM method yielded the following optimal parameters printing speed of 50 mm/s, nozzle temperature of 240°C, layer thickness of 0.30 mm, infill rate of 100%, and bed temperature of 60.65°C